Development of web-based e-LKPD to develop high school students' numeracy on geometry - Aan Subhan Pamungkas; Etika Khaerunnisa; Tania Fajriyanti (Universitas Sarjanawiyata Tamansiswa, 2023)
This development is motivated by the importance of numeracy skills for secondary school students. It is necessary to have learning resources supported by technological developments. However, the facts in the field show that existing learning resources are still conventional and have yet to lead to the achievement of student numeracy. Based on this background, this development aims to develop web-based student worksheets in mathematics learning in secondary schools. This research was conducted at MAN 1 Serang City for grade XI students. The development model used is the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. The instruments used to measure the feasibility of this teaching material are expert validation questionnaires consisting of media experts and material experts, practicality questionnaires, and numeracy tests. Based on the results of processing the expert validation questionnaire, the results obtained are the assessment of media experts in the form of LKPD getting an average percentage score of 85% with very feasible criteria, the assessment of media experts in the form of a web getting an average percentage of 82% with feasible criteria and the assessment of material experts getting an average percentage score of 83% with very feasible criteria. Based on the analysis results, the learner worksheets developed are valid for developing the numeracy of secondary school students.